Supervision and Law Enforcement on Intelligent Transportation Systems on the Highway - Dewi, Nur Kumala (International Journal of Educational Research & Social Sciences, 2021)
This research discusses the supervision and law enforcement on the transportation system, which will be applied to the smart transportation system. With this system, the police and local governments will be able to monitor the transportation system in a city, especially law enforcement on roads. The method used in this study is to use a literature review which is the basis for this research, by using a literature review it will be able to deepen a research, and be able to understand previous studies in order to create new research. The problem raised in this research is how to apply law enforcement on the highway to land transportation, both public vehicles and private vehicles that are on the highway every day, with strict law enforcement it will reduce crime on the road and can reduce accidents on the road Highway. This research will produce a proposed system, which can be used by the police and local governments in enforcing the law on public or private vehicles on the road.